A Glass‐Ceramic with Accelerated Surface Reconstruction toward the Efficient Oxygen Evolution Reaction. Issue 7 (15th December 2020) - Li, Shanlin; Li, Zichuang; Ma, Ruguang; Gao, Chunlang; Liu, Linlin; Hu, Lanping; Zhu, Jinlin; Sun, Tongming; Tang, Yanfeng; Liu, Danmin; Wang, Jiacheng
Abstract: The effective non‐precious metal catalysts toward the oxygen evolution reaction (OER) are highly desirable for electrochemical water splitting. Herein, we prepare a novel glass‐ceramic (Ni1.5 Sn@triMPO4 ) by embedding crystalline Ni1.5 Sn nanoparticles into amorphous trimetallic phosphate (triMPO4 ) matrix. This unique crystalline‐amorphous nanostructure synergistically accelerates the surface reconstruction to active Ni(Fe)OOH, due to the low vacancy formation energy of Sn in glass‐ceramic and high adsorption energy of PO4 3− at the VO sites. Compared to the control samples, this dual‐phase glass‐ceramic exhibits a remarkably lowered overpotential and boosted OER kinetics after surface reconstruction, rivaling most of state‐of‐the‐art electrocatalysts. The residual PO4 3− and intrinsic VO sites induce redistribution of electron states, thus optimizing the adsorption of OH* and OOH* intermediates on metal oxyhydroxides and promoting the OER activity. Abstract : A novel glass‐ceramic (Ni1.5 Sn@triMPO4 ) with unique crystalline‐amorphous nanostructure accelerates the surface reconstruction to form superior OER electrocatalysts, which can be explained by the low vacancy formation energy of Sn atom and high adsorption energy of phosphate anions at O‐vacancy sites. This work showcases the importance of unique glass‐ceramic structure in boosting the surface reconstruction and improving electrocatalytic activity.